The Politics of Covid Vaccine Hesitancy and Opposition. Issue 2 (21st April 2022) - Sorell, Tom; Butler, Jethro
Abstract: Opposition to vaccines is not a new phenomenon, but positions once associated with traditional religious or conservative stances have given way to some highly disparate views that transcend traditional left/right/religious divisions. This article reviews recent literature showing how social media has contributed to the spread of conspiracy theories around Covid‐19 and mass vaccination programmes. The narratives discussed are principally those of the right and the religious right.